2020
DOI: 10.3390/life10070118
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perspective on Alzheimer’s Disease Treatment: Rosmarinic Acid Molecular Interplay with Copper(II) and Amyloid β

Abstract: Alzheimer’s disease is a severe disorder that affects millions of people worldwide. It is a very debilitating disease with no cure at the moment. The necessity of finding an effective treatment is very demanding, and the entire scientific community is putting in a lot of effort to address this issue. The major hallmark of Alzheimer’s disease is the presence of toxic aggregated species in the brain, impaired metal homeostasis, and high levels of oxidative stress. Rosmarinic acid is a well-known potent antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 78 publications
3
18
0
Order By: Relevance
“…The authors concluded that curcumin can simultaneously bind to Cu 2+ and β-amyloid, forming a ternary system. Recently, similar results were also obtained by Kola and co-workers using rosmarinic acid, and the system was characterized via different spectroscopic techniques. Cytotoxic studies revealed that the copper­(II) complex was able to reduce the percentage of cellular viability on NIH3T3 fibroblasts cells.…”
Section: Introductionsupporting
confidence: 76%
“…The authors concluded that curcumin can simultaneously bind to Cu 2+ and β-amyloid, forming a ternary system. Recently, similar results were also obtained by Kola and co-workers using rosmarinic acid, and the system was characterized via different spectroscopic techniques. Cytotoxic studies revealed that the copper­(II) complex was able to reduce the percentage of cellular viability on NIH3T3 fibroblasts cells.…”
Section: Introductionsupporting
confidence: 76%
“…Previously, RA showed several pharmacological properties, including anti‐inflammatory (K. Jiang et al, 2018), antioxidant (Luft et al, 2019), antitumor (Han, Ma, Zhao, Feng, & Zheng, 2019; Messeha, Zarmouh, Asiri, & Soliman, 2020; L. Wang, Yang, Wang, Shi, & Li, 2019), and photoprotection (Sánchez‐Campillo et al, 2009). Furthermore, RA may exert neuroprotective action in the CNS in cases of neurodegeneration (Bhatt, Singh, Prakash, & Mishra, 2015; Hase et al, 2019; Kola, Hecel, Lamponi, & Valensin, 2020; Shan et al, 2015) and mood disorders, including depression and anxiety (Ghasemzadeh Rahbardar & Hosseinzadeh, 2020; Lin et al, 2015). Earlier, using the chronic unpredictable stress model, it was suggested that the antidepressant‐like effect of RA could be related to increase of hippocampal astrocyte BDNF expression through modulation of the extracellular‐regulated kinase (ERK) phosphorylation stress (Jin, Liu, Yang, Zhang, & Miao, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RA was able to suppress Aβ accumulation via dopamine-signaling pathway enhancement [182] and reduce inflammation by downregulating JNK signaling pathway [183]. Recent findings showed that RA interferes with Cu(II)-Aβ complex and forms original ternary association that modifies Aβ reactivity in terms of aggregation and ROS generation [184]. As expected, RA treatment promoted cognitive improvement and neuroprotection against Aβ25- 35 [185], Aβ42 [186,187], and scopolamine [188] induced toxicity in rat model of AD.…”
Section: Rosmarinic Acidmentioning
confidence: 99%